Engagement and affection of pre-service teachers in online learning in the context of COVID 19: engagement-based instruction with web 2.0 technologies vs direct transmission instruction - Basal, Ahmet; Eryilmaz, Ali (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
Due to COVID 19, schools and universities all over the world have gone from full face-to-face lessons to online lessons. This short notice transition has come with many challenges for students including engagement with and affection for the lectures. This study aims to examine whether there is a significant difference between engagement and affection based on instruction types in online virtual class courses. To this end, some Web 2.0 technologies were used in one lecture (GW) and direct transmission in the other lecture (GDT). After 5 weeks, a questionnaire was applied to 92 volunteer participants. Based on the results, while the GW method has a high effect in reducing negative emotions and increasing engagement; it has a moderate effect on the increase of positive affection.
Keywords: Affection; COVID 19; engagement; online education; web 2; 0 technologies; NEGATIVE AFFECT; Education & Educational Research